1986
DOI: 10.1172/jci112670
|View full text |Cite
|
Sign up to set email alerts
|

Translational profiles of alpha 1-, alpha 2-, and beta-globin messenger ribonucleic acids in human reticulocytes.

Abstract: In human reticulocytes, the critical balancing of a-and fl-globin synthesis may be controlled in part by differential translation of the three major adult globin messenger RNAs (mRNAs), al, a2, and ft. In this study, we determined, as a parameter of translational efficiency, the relative ribosome loading of these three mRNAs. Using oligonucleotide probes specific for the al-and a2-globin mRNAs, we find that these two mRNAs have identical translational profiles. Their distribution contrasts with that of j3-glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…It has been demonstrated that the ca2 gene encodes a 2to 3-fold higher steady state level of mRNA than the downstream al gene (Orkin and Goff, 1981;Liebhaber and Kan, 1983;Liebhaber et al, 1985). These levels are also reflected in the protein products of the two genes Shakin and Liebhaber, 1986). The promoters of both a globin genes are identical and their polyadenylation sites are not significantly dissimilar.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the ca2 gene encodes a 2to 3-fold higher steady state level of mRNA than the downstream al gene (Orkin and Goff, 1981;Liebhaber and Kan, 1983;Liebhaber et al, 1985). These levels are also reflected in the protein products of the two genes Shakin and Liebhaber, 1986). The promoters of both a globin genes are identical and their polyadenylation sites are not significantly dissimilar.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies, conducted in the early 1980s, have suggested that in normal persons the amount of a2-mRNA exceeds that of al-mRNA by a factor of 1.5 to 3. perhaps because of a decreased transcription of the alglobin gene (Liebhaber & Kan, 1981: Orkin & Goff, 1981. In a later study, Shakin & Liebhaber (1986) obtained some evidence for an equal translation of the two mRNAs and, based on the higher mRNA levels in reticulocytes, assumed a dominant role for the a2-gIobin gene. suggested that this might be the result of an N 3-fold excess of a2globin mFWA and an N 3-fold higher translational efficiency of the al-globin mRNA, perhaps based on the different structures of the 3' non-coding regions of the two genes.…”
Section: Mutationmentioning
confidence: 93%
“…The α 2 -globin gene seems to have a dominant expression role over α 1 as it encodes approximately 2.6-fold more protein than α 1 [3]. However, recent studies on the expression of the α 1 - and α 2 -globin genes by Molchanova et al [4] have demonstrated that the output of the α 2 -variants is only 1.19 times higher than that of α 1 -variants in heterozygotes with four α-globin genes.…”
Section: Introductionmentioning
confidence: 99%